Testosterone and Cortisol Jointly Predict the Ambiguity Premium in an Ellsberg-Urns Experiment - Danese, Giuseppe; Fernandes, Eugénia; Watson, Neil V.; Zilioli, Samuele (Frontiers in Behavioral Neuroscience, 2017)
Previous literature has tried to establish whether and how steroid hormones are related to economic risk-taking. In this study, we investigate the relationship between testosterone (T) and cortisol (C) on one side and attitudes towards risk and ambiguity on the other. We asked 78 male undergraduate students to complete several tasks and provide two saliva samples. In the task “Reveal the Bag”, participants expressed their beliefs on an ambiguous situation in an incentivized framework. In the task “Ellsberg bags”, we elicited from the participants through an incentive-compatible mechanism the reservation prices for a risky bet and an ambiguous bet. We used the difference between the two prices to calculate each participant’s ambiguity premium. We found that participants’ salivary T and C levels jointly predicted the ambiguity premium. Participants featuring comparatively lower levels of T and C showed the highest levels of ambiguity aversion. The beliefs expressed by a subset of participants in the “Reveal the Bag” task rationalize (in a revealed preference sense) their choices in the “Ellsberg bag” task.